2010
DOI: 10.3986/ac.v39i3.74
|View full text |Cite
|
Sign up to set email alerts
|

UNDERGROUND METEOROLOGY-“What’s the weather underground?”

Abstract: Izvleček UDK 551.44:551.581 Giovanni Badino: Podzemna meteorologija: "Kakšno je vreme v podzemlju?" Namen prispevka je predstaviti nekatere pre�odne pojave, ki vplivajo na jamsko klimo. Pri tem iz�ajam iz osnovni� zakonov fizike in izvirni� eksperimentalni� podatkov. V prvem delu obravnavam povprečne klimatske pogoje v jama� in nji-�ovo povezavo z zunanjo klimo, okoliško kamnine, podzemno vodo ter zunanjo topografijo. Pokažem pomen in vlogo temperaturnega gradienta v jama�. V drugem delu obravnavam pre�odne po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 3 publications
(5 reference statements)
3
139
1
9
Order By: Relevance
“…This high ecological plasticity may explain why the influence of the geological substrate, in constructing the model, is only limited and, in parallel, why topographic heterogeneity is important in explaining the distribution of these spiders. In addition, elevation is likely to act as a surrogate of mean annual temperature, as it directly influences the general thermal conditions found underground (Badino, 2010).…”
Section: Discussion Environmental Drivers Of the Current Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high ecological plasticity may explain why the influence of the geological substrate, in constructing the model, is only limited and, in parallel, why topographic heterogeneity is important in explaining the distribution of these spiders. In addition, elevation is likely to act as a surrogate of mean annual temperature, as it directly influences the general thermal conditions found underground (Badino, 2010).…”
Section: Discussion Environmental Drivers Of the Current Distributionmentioning
confidence: 99%
“…On the other hand, it has been suggested that when a species has newly arrived on a landscape, its M can be estimated only based on dispersal characteristics (Barve et al, 2011). It has been shown that during the early stages of their life cycle, Meta spiders are able to disperse Bio02 and Bio07 represent proxies of the daily and seasonal excursion found in the vicinity of the cave entrance (Badino, 2010) and in other Superficial Subterranean Habitats (Pipan et al 2011;Mammola et al, 2016b), where Meta spiders preferentially thrive. Infiltrating rain water is considered to be the primary factor determining the general climatic conditions found underground (Badino, 2010).…”
Section: Species Distribution Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In deep karst, air flow can also play a major role. Intersecting fluids undergo complex energy exchanges, increasing temperature along their decent through the homothermic layer at a typical "karstic" rate of 3-4°C/km (Badino, 2010). This temperature increase with depth is much lower than the expected value in the case of heat exchanges between air and rock (around 5-6°C/km).…”
Section: Physics Of the Homothermic Layermentioning
confidence: 75%
“…Frogs were more abundant in relatively warm cave sectors. The temperature of cave sectors is the result of complex interactions between external temperature, mean annual temperature, and air circulation of karstic systems (Badino 2004, Badino 2010. In winter, temperature is highest far from the surface, thus these sectors represent ideal shelters during hibernation.…”
Section: Discussionmentioning
confidence: 99%